Modeling and control of a hybrid DC/DC/AC converter to transfer power under different power management strategies - Alizadeh Asl, Amin; Alizadeh Asl, Ramin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
A hybrid DC/DC/AC converter connected to the grid without a three-phase transformer is controlled. The decentralized control method is applied to the hybrid DC-DC converter such that the maximum power of PV flows to the grid side. This controller must charge and discharge the battery at the proper time. It must also regulate DC-link voltage. An additional advantage of the proposed control is that the three-phase inverter does not need a separate controller such as PWM and SPWM. A simple technique is used for creating the desired phase shift in the three-phase inverter, which makes the active and reactive power of the inverter controllable. A new configuration is also proposed to transmit and manage the generation power of PV. In this scheme, the battery and fuel cell are employed as an auxiliary source to manage the generation power of PV. Finally, a real-time simulation is performed to verify the effectiveness of the proposed controller and system by considering the real characteristics of PV and FC.